Keefektivan pendekatan contextual teaching and learning (CTL) untuk meningkatkan kemampuan berpikir kritis dan rasa ingin tahu mahasiswa pada mata kuliah pendidikan Pancasila - Triyani, Triyani (Universitas Negeri Yogyakarta, 2019)
This study aims to develop and apply the Contextual Teaching and Learning (CTL) approach to the Pancasila (civic) education course with the aim of strengthening the attitudes, knowledge, and skills of students regarding Pancasila education. The research output produced is the publication of research results in scientific journals. The research instruments used in this study were a curiosity questionnaire and a description of the questions to test the students' critical thinking skills. The subjects of the trial in this study were 55 sophomore students in the third semester. The effectiveness of the data analysis based on the results of the test was done by determining the percentage of students' mastery learning and determining the gain score <g> in the class used as the research subject. Based on the achievement of mastery learning, classical learning reached 83.64% with the number of students 46 out of 55 students. Gain score <g> is 0.61 or is in the